Stimulation of Bacterial DNA Synthesis by Algal Exudates in Attached Algal-Bacterial Consortia - Murray, Robert E. (Appl Environ Microbiol, 1986)
Algal-bacterial consortia attached to polystyrene surfaces were prepared in the laboratory by using the marine diatom Amphora coffeaeformis and the marine bacterium Vibrio proteolytica (the approved name of this bacterium is Vibrio proteolyticus [W. E. C. Moore, E. P. Cato, and L. V. H. Moore, Int. J. Syst. Bacteriol. 35:382-407, 1985]). The organisms were attached to the surfaces at cell densities of approximately 5 × 10(4) cells cm(-2) (diatoms) and 5 × 10(6) cells cm(-2) (bacteria). The algal-bacterial consortia consistently exhibited higher rates of [(3)H]thymidine incorporation than did biofilms composed solely of bacteria. The rates of [(3)H]thymidine incorporation by the algal-bacterial consortia were fourfold greater than the rates of incorporation by monobacterial biofilms 16 h after biofilm formation and were 16-fold greater 70 h after biofilm formation. Extracellular material released from the attached Amphora cells supported rates of bacterial activity (0.8 × 10(-21) to 17.9 × 10(-21) mol of [(3)H]thymidine incorporated cell(-1) h(-1)) and growth (doubling time, 29.5 to 1.4 days) comparable to values reported for a wide variety of marine and freshwater ecosystems. In the presence of sessile diatom populations, DNA synthesis by attached V. proteolytica cells was light dependent and increased with increasing algal abundance. The metabolic activity of diatoms thus appears to be the rate-limiting process in biofilm development on illuminated surfaces under conditions of low bulk-water dissolved organic carbon. IMAGES: